Public responses to street art paintings along the shophouses in Sungai Petani - Mohamad, Mustaqim Nafiz; Mohd. Hussain, Mohd. Ramzi (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2017)
Expressions of ideology, philosophy or emotions can be manifested into a form of art. The art itself can be in a tangible or intangible form. For street art, it has become a new phenomenon at certain places. Since its existence decades ago, it is interpreted and viewed as a negative influence in certain communities. Street art is confused with graffiti and graffiti tag has been acknowledged as part of vandalism. Different places with different people may have different perceptions on this matter. A study on the response of public about the street art painting in Sungai Petani was conducted to study and understand the significance of street art. The responses are crucial to be considered in order to know whether street art can be accepted and established in Sungai Petani or not. If it does, it will help the development of the state in the future. Nowadays, the street art becomes a significant element due to several situations and places such as (1) a medium of communication; (2) visual culture; and (3) a changing platform. Since the street art started to bloom several years ago, the characteristics of the street art were studied to identify its relationship with public and the places. The result has shown that there were five categories identified; (1) scenery of nature; (2) daily lifestyle; (3) fiction based figure; (4) religion and belief and (5) direct messages.